ANALISIS PENGARUH HARGA INTERNASIONAL, NILAI TUKAR, DAN GDP PERKAPITA AMERIKA SERIKAT TERHADAP NILAI EKSPOR TEKSTIL INDONESIA KE AMERIKA SERIKAT - Perdana, Anisa Putri (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
In an effort to boost economic growth, increased non-migas exports themselves became one way to advance the national economy, seeing the potential of non-Migas Indonesia exports that can be used as a basis product of Indonesian exports. This study was written with the aim of obtaining an analysis of international prices, exchange rates and per capita GDP of the United States against the value of Indonesian textile exports to the US in the years 1989-2018. The methods used in this study are time series and regression model estimates used by OLS (Ordinary Least Square), data processing using eviews 9. Short-term exchange rate variables have a negative effect on the textile export value variable. Textile price index variable has a positive impact on the value of export textile. Per capita GDP variable does not have an effect on export value of textiles. And the long-term variable of exchange value/dollar rate has a negative impact on textile value variables